A flexible metamaterial based on liquid metal patterns embedded in magnetic medium for lightweight microwave absorber. (May 2021) - Lei, Zhenkuang; Tan, Guoguo; Man, Qikui; Ning, Mingqiang; Wang, Shengding; Chen, Shuwen; Yang, Zhen; Li, Run-Wei
Graphical abstract: Highlights: The metamaterial absorber achieved maximum microwave absorption of −23.36 dB at 0.9 mm thickness and 1.91 g/cm 3 density. The metamaterial absorber can maintain good absorption performance after multiple bending. Liquid metal replaces solid metal so that the absorber has good resistance to bending fatigue. This work provides a strategy for reducing weight and thickness by bonding magnetic materials and metamaterials. Abstract: Lightweight electromagnetic absorbing materials with thinner thickness and low density are highly desired for practical applications. In this work, a thin and lightweight magnetic metamaterial absorber was proposed by embedding liquid metal resonant patterns in magnetic composites medium with a low filling rate. Due to the coupling of magnetic medium and metamateria as demonstrated by CST (Computer Simulation Technology) simulation, the strong electromagnetic resonant loss and multiple reflections were rationally introduced. The obtained metamaterial absorber endows the strong absorption performance of −23.63 dB, an effective absorption bandwidth (EAB, with RL less than −10 dB) of 2.46 GHz under 0.9 mm and with a 1.91 g/cm 3 density merely. The introduction of resonance patterns in the magnetic composites medium is an efficient way to fabricate lightweight and thin thickness metamaterials for high-performance microwave absorbers.